Green factory: is it improving environmental burden? survey result in Malaysia - Ahmad, Md Fauzi; Ishak, Mohd Hafizal; Abdul Hamid, Nor Aziati; Mohd Rasi, Raja Zuraidah Raja; Muhd Nor, Nik Hisyamudin (American Scientific Publishers, 2018)
Green Factory is a new and proactive approach to reduce environment burden. Physical development grew rapidly has effected major implications to environment. Environmental issues such as carbon dioxide, loss of biodiversity, degradation of natural resources, global warming, ozone layer depletion and deforestation have effected on the environment stability. Based on statistics, showing amount of carbon dioxide gas production in Malaysia was 29 million tonnes which Malaysia is ranked 26th (0.66%) of the 215 countries in the world. 110 world leaders including Malaysia has agreed to work for reducing carbon dioxide gas in the Copenhagen Climate Change Summit 2009. Accordingly, a study was conducted on companies that adopted Green Factory practices to assess its key performance criteria and practices for minimizing environmental problems. The samples were 300 companies in Malaysia. Finally, 20% response rate has been received, with 60 respondents. Five main criteria for Green Factory have been identified; (1) Solar power generation systems, (2) Fuel cells system, (3) Cogeneration systems, (4) Air conditioning units and (5) Recycling system. Based on descriptive result, recycling shows the highest level of practices, followed by solar power cogenerations system, air conditioning units and fuel cells system. This study result shows Green Factory has significant relationship with environment performance (r = 0.404, P < 0.05) and business performance (r = 0.38, P < 0.05). Overall, the survey result shows green factory practices is well implemented in Malaysia manufacturing companies. In conclusion, Green Factory can be used as effective tool for improving not only for environment performance but also for business performance.